2011
DOI: 10.12659/msm.881436
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of ventricular arrhythmia using new parameters based on high resolution body surface potential mapping

Abstract: SummaryBackgroundThe effective screening of myocardial infarction (MI) patients threatened by ventricular tachycardia (VT) is an important issue in clinical practice, especially in the process of implantable cardioverter-defibrillator (ICD) therapy recommendation. This study proposes new parameters describing depolarization and repolarization inhomogeneity in high resolution body surface potential maps (HR BSPM) to identify MI patients threatened by VT.Material/MethodsHigh resolution ECGs were recorded from 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Healthy volunteer was examined in supine position. The 67-lead, high-resolution electrocardiographic mapping system was used for ECG recordings [39,40]. Passive electrodes were positioned around the patient's torso according to the diagram shown in Fig.2.…”
Section: Subject and Methodsmentioning
confidence: 99%
“…Healthy volunteer was examined in supine position. The 67-lead, high-resolution electrocardiographic mapping system was used for ECG recordings [39,40]. Passive electrodes were positioned around the patient's torso according to the diagram shown in Fig.2.…”
Section: Subject and Methodsmentioning
confidence: 99%
“…It is defined as a beat-to-beat change in the Twave amplitude that repeats every other heart beat and indicates the spatial heterogenity of the ventricular repolarization. Both temporal and spatial distribution of the electrical potentials generated by heart on the surface of the body could be investigated by high resolution body surface potential mapping (HR-BSPM) [8][9]. In the presented study the results of the TWA assessment by using FFT-based method are shown [10].…”
Section: Introductionmentioning
confidence: 98%
“…At present, there is no generally accepted non-invasive risk index. T-wave alternans (TWA) is a very promising marker of the vulnerability to ventricular arrhythmia often leading to SCD [6], [7]. It is defined as a beat-to-beat change in the T-wave amplitude that repeats every other heart beat and indicates the spatial heterogeneity of the ventricular repolarization.…”
Section: Introductionmentioning
confidence: 99%
“…Both temporal and spatial distribution of the electrical potentials generated by the heart on the surface of the body can be investigated by high resolution Body Surface Potential Mapping (BSPM) [7]- [9]. BSPM is the most promising method of extending medical utility of ECG.…”
Section: Introductionmentioning
confidence: 99%